2017
DOI: 10.1159/000457946
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation/Dose Reduction of Angiotensin-Converting Enzyme Inhibitors/Angiotensin Receptor Blockers during Acute Decompensated Heart Failure in African-American Patients with Reduced Left-Ventricular Ejection Fraction

Abstract: Objectives: Patients with heart failure (HF) and reduced left-ventricular ejection fraction (LVEF) benefit from angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blocker (ARB) therapy. While dose reduction/discontinuation (r/d) of β-blockers (BB) and furosemide in acute decompensated HF (ADHF) worsen outcomes, data on ACEI/ARB are lacking. Methods: To determine the frequency and reasons for ACEI/ARB therapy r/d in ADHF patients, we studied 174 patients with LVEF <40% on ACEI/ARB and BB t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…Importantly, there was a lack of association RASB therapy was reduced or discontinued in 17.2% of patients due to acute kidney injury (56.7%), hypotension (23.3%), and hyperkalemia (10%). 20 Admission creatinine and SBP were both associated with RASB discontinuation and nonuse. Although the rationale for RASB discontinuation or nonuse was unknown in our cohorts, the lack of an association between RASB prescription and systolic blood pressure suggests that hypotension may not be the primary impetus for RASB discontinuation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Importantly, there was a lack of association RASB therapy was reduced or discontinued in 17.2% of patients due to acute kidney injury (56.7%), hypotension (23.3%), and hyperkalemia (10%). 20 Admission creatinine and SBP were both associated with RASB discontinuation and nonuse. Although the rationale for RASB discontinuation or nonuse was unknown in our cohorts, the lack of an association between RASB prescription and systolic blood pressure suggests that hypotension may not be the primary impetus for RASB discontinuation.…”
Section: Discussionmentioning
confidence: 97%
“…Practice patterns underlying RASB discontinuation and nonuse vary without clear supporting evidence currently to justify reasoning, particularly in patients who remain hemodynamically stable. In a cohort of 174 patients admitted with ADHF, Kane et al showed that RASB therapy was reduced or discontinued in 17.2% of patients due to acute kidney injury (56.7%), hypotension (23.3%), and hyperkalemia (10%) . Admission creatinine and SBP were both associated with RASB discontinuation and nonuse.…”
Section: Discussionmentioning
confidence: 99%
“…1,10 Therapeutic measures that can lead to WRF, such as the use of ACEIs/A2RBs, may not necessarily increase the mortality associated with CRS1, and under certain circumstances may even improve clinical outcome. 8,15,24,25 Therefore, teasing apart the interaction and independent roles of CRS1 and ACEI/A2RB usage in determining in-hospital mortality among patients admitted with ADCHF can be extremely challenging.…”
Section: Discussionmentioning
confidence: 99%
“…1,6 Management of ADCHF is complicated by the fact that CRS1 or concerns regarding its development often limit the use of common therapeutic strategies, such as inhibition of the renin-angiotensin-aldosterone system (RAAS) and/or escalation of diuretic therapy. 5,[7][8][9] Although WRF may be transient in ADCHF patients, RAAS inhibition and/or escalation of diuretic therapy may in themselves lead to WRF, further complicating the clinical picture. [10][11][12][13][14] An important question for patients hospitalized with ADCHF is at what level of WRF RAAS inhibitions lose its survival advantage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation